PANDANGAN HINDU TERHADAP PEMIKIRAN KEFILSAFATAN PYTHAGORAS - I Putu Agus Aryatnaya Giri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
There is a similarity to the concept of philosophical thinking between Pythagoras and Hinduism. just call the first that Pythagoras believed in the existence of the Soul and the transfer of souls from the present being to the creatures to come. When someone dies, his soul returns to the world, enters the body of one animal. Hindus themselves know these teachings as Punarbhawa or Samsara which are part of Panca Sraddha. On the other hand, Pythagoras also stated that in order to achieve a pure life, one must eat meat and beans. With his belief, Pythagoras became an advocate of vegetarianism, which only ate vegetables and fruits, which in Hinduism were included in the teachings of ahimsa.